What matters most to people in musculoskeletal physiotherapy consultations? A qualitative study. (June 2018) - Stenner, Rob; Palmer, Shea; Hammond, Ralph
Abstract: Background: Person-centred approaches to care require clinicians to engage in trying to understand the full range of problems and concerns, treatment and investigation requests, and emotional and social issues that people bring to the consultation. If, however, the main issues of importance are not openly declared and discussed they cannot be addressed. This is likely to result in people receiving the care that clinicians think they need, rather than care based on individual needs and preferences. Objective: To understand people's abilities to express the issues of importance to them within a consultation and clinicians' abilities to acknowledge and address those issues. Design: A qualitative study using an interpretive phenomenological approach. Methods: Fifteen people and their physiotherapists were interviewed and their consultations recorded. The resulting data sets were analysed to identify and report themes within the data. Findings: The findings revealed that people present with what are often simple issues, but which are sometimes expressed in an unstructured way in clinical encounters and are often difficult for clinicians to establish. Three linked themes emerged: (1) clear versus unstructured agendas; (2) people need information and understanding; and (3) developing a sense of collaboration. Conclusions: The issues of importance that people bring to a consultation are varied and often vague. This research highlights the importance of communication to elicit, identify and address the issues of importance to people in clinical encounters to ensure a positive experience and outcome for both the individual person and clinician. Tweetable Abstract: Achieving desirable health outcomes is more likely when people are supported to think about their priorities and 'what matters to them'. Highlights: Communication within physiotherapy is underexplored and frequently overlooked. Understanding what is important to a person is vital to ensure a positive outcome. People's issues are often simple but are sometimes voiced in an unstructured way. Clinicians need to better support people to elicit 'what matters to them'. Meaningful conversations may encourage an active role for people in their care.